Предмет: Алгебра,
автор: Gumanitariy1
Сократите, пожалуйста
Приложения:
Ответы
Автор ответа:
0
1)
(√x - √y) / ((√x)² - (√y)²) = (√x - √y) / [(√x - √y)(√x + √y)]= 1/(√x + √y)
2)
((⁴√a)² - (⁴√b)²) / (⁴√a + ⁴√b) =[(⁴√a - ⁴√b)(⁴√a + ⁴√b)] / (⁴√a + ⁴√b)=
=⁴√a - ⁴√b
(√x - √y) / ((√x)² - (√y)²) = (√x - √y) / [(√x - √y)(√x + √y)]= 1/(√x + √y)
2)
((⁴√a)² - (⁴√b)²) / (⁴√a + ⁴√b) =[(⁴√a - ⁴√b)(⁴√a + ⁴√b)] / (⁴√a + ⁴√b)=
=⁴√a - ⁴√b
Похожие вопросы
Предмет: Химия,
автор: Аноним
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Українська мова,
автор: vasiiabatareika
Предмет: Литература,
автор: 568545